Pengaruh Harga, Kualitas Pelayanan, dan Inovasi Desain Terhadap Loyalitas Pembelian Merk Minorfighters - Panjaitan, Roymon (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
The increasing growth of retail products in Indonesia has led to the increasing level of competition in the retail business faced by domestic products. The usefulness of this research is to detect the influence of price levels, service quality and design innovation on purchase loyalty that exists in the Minorfighters brand. The researcher took a sample of 87 respondents using the purposive sampling method. Data collection using questionnaires and interviews. Data is processed using validity test, reliability test, cross tabulation analysis, correlation coefficient, coefficient of determination, simple and multiple regression analysis, and significance test. The results showed that the existence of price factors, service quality and design innovations that positively influence purchase loyalty. Design innovation variables have a greater influence on purchase loyalty. This result is the initial hypothesis of the authors examined in this paper.